The american urological association’s prostate cancer screening guideline: Which cancers will be missed in average-risk men aged 40 to 54 years? - Moody, Thomas E. (Rev Urol, 2017)
To determine the impact of the American Urological Association’s (AUA) guideline for early detection of prostate cancer that recommends against routine screening in men aged 40 to 54 years at average risk (eg, white men without a family history of prostate cancer), we undertook a study of 973 men who previously underwent a prostate biopsy at Urology Centers of Alabama (UCA) over the 5-year period from 2010 to 2014. We retrospectively reviewed the results of the prostate biopsies performed by urologists at UCA—and, where applicable, the final surgical pathology results and compared the results by race and family history. In white men with a family history of prostate cancer, 47% had cancer and 30% had Gleason score (GS) ≥ 7 disease. In white men without a family history of prostate cancer, 32% had cancer and 23% had GS ≥ 7 disease. By comparison, in African American men with a family history of prostate cancer, 56% had cancer and 42% had GS ≥ 7 disease. In African American men without a family history, 42% had cancer and 29% had GS ≥ 7 disease. In our study, 144 of 456 (32%) of the group of average-risk men had cancer and 105 of 456 (23%) had GS ≥ 7 cancer. Had the AUA guidelines been followed, these cancers would have been missed or the diagnoses delayed.